Innovations in rural and agricultural finance: Determinants of microcredit repayment in federations of Indian self-help groups - Deininger, Klaus; Liu, Yanyan (International Food Policy Research Institute, 2010)
Since the establishment of the Grameen Bank in Bangladesh in 1976, microfinance has boomed. As of December 31, 2007, 3,552 microcredit institutions had reached 154 million clients worldwide, about 106.6 million of whom were among the poorest when they took their first loan. Such expansion can be at least partly attributed to the widely adopted practice of group lending in microfinance programs. In contrast to individual lending, group lending (or joint liability) grants a loan to a group of borrowers, and the whole group is liable for the debt of any individual member in the group. This practice allows microfinance programs to rely mainly on accountability and mutual trust among group members rather than financial collateral to insure against default. Given that the poor often lack appropriate financial collateral, group lending programs offer a feasible way of extending credit to poor people who are usually kept out of traditional banking systems.